Trabalhadores da Albras e sua organização política - GOMES, Vera Lúcia Batista (2012)
As of the late 20th century and beginning of the 21st century, workers organizations have deeply changed. Workers struggle to defend their interests and those of the society in general have become more and more difficult. This study analyzes the particularities of the present status of Albras workers political organization, based on the changes undergone by the company, and how those changes affected the Metal Industry Workers Union of the State of Pará (SIMETAL). It tries to understand the challenges to the workers collective actions towards a new structure within the industrial capitalism.